The Role of The Young Generation In Stunting Prevention To Create Superior Human Resources In Abang Village, Abang District, Karangasem Regency - Marhaeni, A.A.I.N; Nyoman Yuliarmi, Ni; Jati Primajana, Dewa; Pradnyadewi, Diah; Ketut Sudibia, I; Kadek Eka Jayanthi, Ni; Sinthya Aryasthini M, Made; Nyoman Reni Suasih, Ni; Santana Putra A, Made (International Journal Of Community Service, 2023)
Addressing and reducing the prevalence of stunting in Indonesia, supported by the reduction of stunting in various regions throughout the country, is a highly relevant program in achieving Indonesia's vision for 2045 as declared by the President of the Republic of Indonesia. In realizing this vision, the program to reduce the prevalence of stunting in Indonesia becomes highly relevant to achieve this overarching goal. Therefore, all elements of society, in accordance with their respective roles, can contribute to supporting the realization of Indonesia's advanced vision. Hence, studies regarding the condition of stunting in its various dimensions become very important and relevant. The purpose of this Community Engagement activity is to: 1) Analyze the knowledge, attitudes, and practices of young generations in stunting prevention in a rural village; 2) Enhance the role of young generations in stunting prevention in their village. The Community Engagement activity was conducted in Abang Village, Karangasem Regency. This regency was chosen because it has the highest prevalence of stunting among the regencies in Bali Province. The activity involved young people in the village, known as "Sekehe Teruna Teruni," as participants in the event, which provided Communication, Information, and Education (KIE) related to stunting prevention. There were three resource persons for this activity, including an academic, a healthcare professional, and a Family Planning field educator. After the socialization, an evaluation was conducted on the participants, and the results were analyzed using descriptive statistics. The analysis revealed the following: 1) About 70% of the participants had heard of the stunting phenomenon, while the remaining 30% had not. Approximately 96% of the participants increased their knowledge about stunting after the KIE, with only about 4% not experiencing an increase in their knowledge. This increase in knowledge influenced their attitudes, making them more willing to participate in stunting prevention through family planning, 2) Data analysis indicated that all participants, 100%, expressed their intent to plan the number of children they would have when they get married according to their economic and other capabilities. Generasi muda berperan penting dalam penurunan/ pencegahan stunting karena generasi muda ini yang akan melahirkan anak-anak nantinya sehingga dapat dijaga kualitas anak yang dilahirkan sehingga stunting dapat dicegah/ diturunkan dengan peran dari generasi muda tersebut.